Towards Building a Quantitative Proteomics Toolbox in Precision Medicine: A Mini-Review - Correa Rojo, Alejandro; Heylen, Dries; Aerts, Jan; Thas, Olivier; Hooyberghs, Jef; Ertaylan, Gökhan; Valkenborg, Dirk (Frontiers in Physiology, 2021)
Precision medicine as a framework for disease diagnosis, treatment, and prevention at the molecular level has entered clinical practice. From the start, genetics has been an indispensable tool to understand and stratify the biology of chronic and complex diseases in precision medicine. However, with the advances in biomedical and omics technologies, quantitative proteomics is emerging as a powerful technology complementing genetics. Quantitative proteomics provides a dynamic range of wellbeing and disease because proteins represent intermediate phenotypes and provide direct biological insights into physiological patterns, while genetics accounting for baseline characteristics. Additionally, quantitative proteomics opens a wide range of applications in clinical diagnostics, treatment stratification, and drug discovery. In this mini-review, we discuss the current status of quantitative proteomics in precision medicine including the available technologies and common methods to analyze quantitative proteomics data. Furthermore, we highlight the current challenges to put quantitative proteomics into clinical settings and provide a perspective to integrate proteomics data with genomics data for future applications in precision medicine.